Variación espacio-temporal de las larvas de tres especies de peces migratorios en el cauce del río Magdalena (Colombia), durante el ciclo hidrológico 2006-2007 (2014)
ABSTRACT: In the middle Magdalena river drainage (Colombia) samples were taken weekly during the 2006-2007 hydrological cycle to assess the spate-temporal variation of the larvae of three species of migratory fish (Prochilodus magdalenae Steindachner 1877, Pimelodus spp. Y Pseudoplatystoma magdaleniatum Buitrago-Suarez y Burr 2007). For this analysis we considered the abundance and density of individuals in each of the samples taken in the main channel of the Magdalena River at Puerto Berrio (Antioquia). A total of 490 individuals were captured, with Pimelodus app. exhibiting the greatest abundance (74.7%), followed by P. Magdaleniatum (13.7%), and P. Magdalenae (11.6%). We found that the abundance and density of larvae among sites were homogeneous and significant differences were only encountered between hydrological periods associated with the interaction of physical factors such as an increase in the water level.